Supercyclicity of multiplication on Banach ideal of operators - Mohamed Amouch; hamza Lakrimi (Boletim da Sociedade Paranaense de Matemática, 2022)
Let X be a complex Banach space with dim X > 1 such that its topological dual X∗ is separable and B(X) the algebra of all bounded linear operators on X. In this paper, we study the passage of property of being supercyclic from T ∈ B(X) to the left and the right multiplication induced by T on an admissible Banach ideal of B(X). Also, we give a sufficient conditions for the tensor product T ⊗bR of two operators on B(X) to be supercyclic.